Congenital hypothyroidism in India: A systematic review and meta-analysis of prevalence, screen positivity rates, and etiology - Rajendra Prasad Anne; Emine A. Rahiman (Elsevier, 2022)
Summary: Background: Congenital hypothyroidism (CH) is the leading cause of preventable mental retardation, which is currently not universally screened in India. Knowledge of the country-specific prevalence of the disease can guide in establishing a universal screening program. Methods: We performed a systematic review and meta-analysis to assess the prevalence, screen positivity rates, compliance to recall and etiology of CH in India. The databases of PubMed, Embase, Google scholar and IMSEAR were searched on 1st October 2021. All observational studies reporting at least one of the outcomes of interest were included. Two reviewers independently extracted the data and appraised the quality of studies using the Joanna Briggs tool for prevalence studies. Estimates were pooled using a random-effects model with double arcsine transformation (MetaXL software). PROSPERO database registration number was CRD42021277523. Findings: Of the 2 073 unique articles retrieved, 70 studies were eligible for inclusion. The prevalence of CH (per 1 000 neonates screened) was 0·97 (95% confidence intervals/CI: 0·9, 1·04) in non-endemic areas (54 studies and 819 559 neonates), 79 (95% CI: 72, 86) in endemic areas (3 studies, 5 060 neonates), 50 (95% CI: 31, 72) in neonates born to mothers with thyroid disorders, and 14 (95% CI: 8, 22) in preterm neonates. At thyroid stimulation hormone cut-off of 20 mIU/L, the screen positivity rates were 5·6% (95% CI: 5·4%, 5·9%) for cord blood samples and 0·19% (95% CI: 0·18%, 0·2%) for postnatal sample. About 70% (95% CI: 70, 71) of screen positive neonates were retested with diagnostic tests. Among neonates with permanent hypothyroidism, thyroid dysgenesis 56·6% (95% CI: 50·9%, 62·2%) was more common than dyshormonogenesis 38·7% (95% CI: 33·2%, 44·3%). Interpretation: The prevalence of congenital hypothyroidism in India is higher than global estimates. Screen positivity rate was higher for cord blood screening when compared to postnatal screening. Compliance with confirmatory testing was higher for cord blood screening. Funding: The study was not funded by any source.